Optimization of Turning Process Parameter for GFRP through CNC Turning Process - Babu, R. S.; Parthasarathy, C.; Chandradass, J. (Asian Review of Mechanical Engineering, 2015)
Nowadays, glass fiber reinforced plastics (GFRP) composites play a vital role new line in many engineering applications as an alternative to various heavy exotic materials. Newline in GFRP polymeric composites, the matrix of polymer (resin) is reinforced with glass line fibers. Glass fiber reinforced plastics are increasingly used for variety of engineering new line applications from automobile to air craft components because of their superior new line advantages when compared to the other engineering materials. Turning of GFRP composite materials is a rather complex task owing to its heterogeneity and the number of problems. The Problems are surface delimitation, which appear during the machining process that is associated with the characteristics of the material and the cutting parameters. Optimization of machining parameters is an important process in machining. Experiments were conducted based on the established Taguchi’s technique L9 orthogonal array on a lathe machine. The cutting parameters are speed, feed rate, and depth of cut on the surface roughness, machining timing and material removal rate produced. The performances of the various parameters are evaluated by measuring surface roughness and material removal rate. The results indicate that the developed model is suitable for prediction of surface roughness and material removal rate in machining of glass fiber reinforced plastics composites. The percentage of contribution was analyzed speed parameter 80% for surface roughness feed parameter 66%for machining timing s and feed parameter 64% for MRR.